Coral Reef Restoration for Coastal Protection: Water Quality Monitoring in Indonesia Coral Reef Garden Nusa Dua, Bali - Burhanuddin, Safri; Badriana, Mochamad Riam; Nur, Ashadi Arifin; Abdurrahman, Umar; Jeon, Chungkyun; Radjawane, Ivonne Milichristi; Park, Hansan; Hutahaean, Andreas Albertino (Geological Agency, 2024)
The Indonesia Coral Reef Garden (ICRG) is a coral reef restoration program with Nusa Dua as one of five sites in Bali. A plantation program has been done by 2020, but it is necessary to monitor the condition. A field survey in Nusa Dua was carried out on October 3-4, 2022 to measure and check ocean parameters that are suitable for coral life and diving in artificial coral reefs installed. In the survey, several points had been measured through CTD Valeport Midas+ prior to measuring ocean parameters in the same location as a preliminary survey done two years in advance. The sea condition of temperature, salinity, pH, turbidity, and DO is 24.89 - 28.69 °C, 33.75 - 34.22 psu, 8.0 - 8.1, 1.19 - 4.27 FTU, and 4.47 - 5.24 mg/L, respectively. Based on the conformity of water quality, the water condition is good for coral growth. A total of 15 locations are used to put artificial coral reefs in many forms or structures. The coral plantation program in Nusa Dua shows promising progress in qualitatively consisting of species of Montipora sp., Acropora sp., and Alcyonacea sp. A continuous measurement is demanded to monitor the condition of coral growth quantitatively.